Gait characteristics of individuals with transtibial amputations walking on a destabilizing rock surface - Gates, Deanna H.; Dingwell, Jonathan B.; Scott, Shawn J.; Sinitski, Emily H.; Wilken, Jason M. (Gait & posture, 2012)
► 13 Patients with transtibial amputations walked on level ground and a loose rock surface. ► Patients took shorter, wider steps on the rock surface. ► Patients increased hip and knee flexion, to increase toe clearance when walking on the rocks. ► Patients made adaptations on the rocks that were asymmetric, and initiated proximally. Individuals with transtibial amputation (TTA) have a high incidence of falls during walking. Environmental factors, such as uneven ground, often play a contributing role in these falls. The purpose of this study was to quantify the adaptations TTA made when walking on a destabilizing loose rock surface. In this study, 13 young TTA walked over a rock surface and level ground at four controlled speeds. Subjects successfully traversed the rock surface by adopting a conservative gait characterized by shorter and wider steps. They also took shorter steps with their prosthetic limbs and exhibited greater variability in foot placement when stepping onto their intact limb. Between-limb differences in step length and width variability increased at faster walking speeds. TTA increased hip and knee flexion during initial stance, which contributed lowering the whole-body center of mass. TTA also increased hip and knee flexion during swing, enabling them to significantly increase their toe clearance on the rock surface compared to level ground. Toe clearance on the prosthetic side was aided by increased ipsilateral hip flexion. The results suggest that TTA were able to adapt their gait to overcome the challenge imposed by the rock surface. These adaptations were asymmetric and initiated proximally.